1998
DOI: 10.1046/j.1365-8711.1998.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Microarcsecond instability of the celestial reference frame

Abstract: The fluctuation of the angular positions of reference extragalactic radio and optical sources under the influence of the irregular gravitational field of visible Galactic stars is considered. It is shown that these angular fluctuations range from a few up to hundreds of microarcseconds. This leads to a small rotation of the celestial reference frame. The nondiagonal coefficients of the rotation matrix are of the order of a microarcsecond. The temporal variation of these coefficients due to the proper motion of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…On the other hand, Klioner [83] points out that unpredictable microlensing noise can spoil the determination of positions and proper motions of the objects resulting from future astrometric missions on a submicroarcsecond level. The gravitational image motion (GIM) due to microlensing effects may be comparable to proper motion of quasars [8,9,[84][85][86].…”
Section: Preliminary Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Klioner [83] points out that unpredictable microlensing noise can spoil the determination of positions and proper motions of the objects resulting from future astrometric missions on a submicroarcsecond level. The gravitational image motion (GIM) due to microlensing effects may be comparable to proper motion of quasars [8,9,[84][85][86].…”
Section: Preliminary Commentsmentioning
confidence: 99%
“…Unlike the previous sections, here we rule out strong microlensing events that are accompanied by a considerable brightness amplification. In some situations it will be difficult to separate GIM from real proper motions, and this is important for accuracy of the fundamental reference frame based on extragalactic sources [83,85,86]. The gravitational field of point masses (which is essentially inhomogeneous) induces a stochastic motion of the source image in the reference frame of the source.…”
Section: Statistical Effect Of Gravitational Dragging Of a Distantmentioning
confidence: 99%
“…Such angular fluctuations may range up to hundreds of microarcseconds. Sazhin et al (1998) found a good example of a quasar with large positional uncertainties caused by the lensing effects of a nearby Hipparcos star; the distance of the star is very close, just 50 pcs. Figure 16 shows a contour plot of number of sources which have an astrometric or photometric variation caused by microlensing of the same order of magnitude as the mission target accuracy.…”
Section: Noise Caused By Microlensingmentioning
confidence: 99%
“…Microlensing noise is a fundamental limit to the accuracy to which we can know the positions of sources. For example, Sazhin et al (1998Sazhin et al ( , 2001 have pointed out that fluctuations of the angular positions of reference extragalactic radio and optical sources will be caused by the microlensing effects of stars in the Galaxy. Such angular fluctuations may range up to hundreds of microarcseconds.…”
Section: Noise Caused By Microlensingmentioning
confidence: 99%
“…As a related work, the fluctuation of the angular positions of reference extragalactic radio and optical sources under the influence of the irregular gravitational field of visible Galactic stars is considered by Sazhin et al (1998). The fluctuation leads to a small rotation of the celestial reference frame.…”
Section: Introductionmentioning
confidence: 99%